دراسة التأثيرات المحتملة لنوعية العائل النباتي في فاعلية المبيدات تجاه الأكاروس Tetranychus urticae Koch (Tetranychidae: Acari) - صقر إبراهيم; الرهبان بهاء; فيوض دينا (Latakia University Journal -Biological Sciences Series, 2018)
يعتبر الأكاروس Tetranychus urticae Koch من الآفات التي لا تزال تحدث أضراراً كبيرة على زراعات كثيرة, رغم تنوع الإجراءات المستعملة لمكافحته. ونظراً لاستمرار الاعتماد على استخدام الأسلوب الكيميائي, فإن البحث يهدف إلى توضيح التباين المحتمل في درجة تأثير المبيد وفقاً لنوع وفصيلة العائل النباتي. وقد أظهرت النتائج باستعمال الأقراص الورقية (Leaf disk) المأخوذة من ستة عوائل تتبع ثلاث فصائل, وجود فروق معنوية بين درجات التأثير اليومية والمتوسطات النهائية لفاعلية المبيدين Fenpyroximate و Fenazaquin في عائلي الفصيلة الفراشية (Phaseolus vulgaris L. Vicia faba L.)، وفي عائلي الفصيلة القرعية (Cucumis sativus L. , Cucurbita pepo L.) وبالنسبة لـ Fenpyroximate. فقد كانت الفروق معنوية بين بعض درجات التأثير اليومية فقط للمركبات Fenazaquin وDimethoate في عائلي الفصيلة الباذنجانية (Solanum melongena L. , Lycopersicum esculentum Mill.)، Fenpyroximate, Pyridaben وAbamectin على عائلي الفصيلة القرعية. وأوضحت النتائج ضرورة أخذ العائل النباتي بالاعتبار عند استخدام المبيدات ودراسة فعاليتها. Tetranychus urticae Koch is considered of the pests that damage many crops severely in spite of the procedures used to control it. Because of the on going dependence on using the chemical methods, this research aims to clarify the potential difference in the degree of the pesticide influence according to the kind of plant host. Leaf disks from six hosts for three families were used. Results showed presence of significant differences between the daily degrees of influence, and the final averages of the two pesticides efficiency Fenpyroximate and Fenazaquin in the two hosts from Fabaceae (Phaseolus vulgaris L. Vicia faba L.) in two hosts from Cucurbitaceae (Cucumis sativus L. , Cucurbita pepo L.) for Fenpyroximate. The differences were significant between daily degrees of influence only for the compounds of Fenazaquin and Dimethoate on two hosts of Solanaceae, (Solanum melongena L. , Lycopersicum esculentum Mill.) Fenpyroximate, Pyridaben, and Abamectin in two hosts of Cucurbitaceae. Results showed the necessity of considering the plant host when studying efficiency of the pesticides and using them.